Determinants of sovereign credit ratings in an emerging economy: A case of South Africa - Sibanda, Michael (Graduate School of Business (GSB), 2018)
The author attempts to identify and measure determinants of sovereign credit ratings for emerging markets as rated by the three leading ratings agencies, namely:- Fitch, Moody's, and Standard and Poor's. Sovereign credit ratings have a vital role in capital mobilisation and portfolio inflows as they dictate the cost and eligibility of borrowing in the global capital markets. The sovereign credit ratings also act as a ceiling for sub-sovereign borrowers’ foreign currency ratings, and as suggested by available literature and empirics, sub-sovereigns can never be rated above their sovereign. Emerging markets now account for 40 percent of the world GDP, up from around 20 percent two decades ago. However, despite the strong foreign investment inflows to emerging markets, according to Standard and Poor’s 2016 report, 9 of the top 20 emerging market sovereigns had negative outlook on their credit ratings, thus indicating a possible downgrade over the next two years. Since 2010, South Africa’s sovereign foreign currency ratings have generally been stable to negative, with some downgrades in 2013 and 2015. For the past decade, South Africa has moved from BBB+ to BBB- as at end of 2016. Drawing on the literature, the analysis shows a formalised relationship between certain economic variables and the sovereign credit ratings. Economic variables like economic growth, exchange rate and the country’s external balance of payments have a positive impact on credit ratings, whilst a negative relationship exists between sovereign ratings and variables like inflation and external debt. Based on these findings, a case can be made in assisting emerging and developing countries to obtain and or achieve investment grade credit ratings, not just for central government borrowing, but for local and other sub-sovereign entities' access to international capital markets. Improved ratings can also be useful for securitization and in leveraging official aid and improved borrowing terms for emerging and developing markets.